Penginjilan di Pedalaman Kalimantan Barat - Ketty (ICHTUS: Jurnal Teologi dan Pendidikan Kristiani, 2021)
Abstract: Evangelism is God's command written in the book of Matthew 28:19-20 which is known as theGreat Commission. One task is to preach the good news or news of salvation in Jesus Christ. This is doneby calling it out and can also be done by teaching like a student and by testifying based on what thepreacher of the Gospel experienced. Evangelism is desired by God as a task that is carried out collectivelyand continuously in all places until Jesus comes a second time to pick up His people. Failure to carry outthis Great Task means violating God's will or denying the grace that has been received. The task ofevangelism cannot be denied or neglected because the news concerns the salvation of the souls of manypeople loved by the Giver of the command, in this case God himself. However, various obstacles areencountered when evangelism is carried out in a community in a certain area. Evangelists must findeffective ways or strategies to ensure that the Gospel being preached is accepted by listeners. Evangelismcarried out specifically by Indonesian evangelists in several remote areas in West Kalimantan must applyan effective evangelism model to overcome various obstacles in conveying the Gospel.Keywords: evangelism, models, obstacles and solutions.Abstrak: Penginjilan merupakan perintah Allah yang tertulis dalam kitab Matius 28:19-20 yangdikenal dengan Amanat Agung. Satu tugas untuk memberitakan kabar baik atau kabarkeselamatan di dalam Yesus Kristus. Dilakukan dengan cara menyerukannya dan dapat jugadilakukan dengan mengajar seperti kepada seorang murid serta dengan bersaksi berdasarkan apayang dialami oleh pemberita Injil tersebut. Penginjilan dikehendaki Allah sebagai tugas yangdilaksanakan secara bersama-sama dan terus-menerus ke segala tempat sampai Yesus datangkedua kali untuk menjemput umat-Nya. Kelalaian melaksanakan Tugas Agung tersebut berartimelanggar kehendak Tuhan atau pengingkaran terhadap anugerah yang telah diterima. Tugaspenginjilan tidak dapat dibantah atau dilalaikan karena berita itu menyangkut keselamatan jiwabanyak orang yang dikasihi oleh Pemberi perintah dalam hal ini adalah Allah sendiri. Tetapiberbagai hambatan ditemui saat penginjilan dilakukakan pada suatu masyarakat dalam daerahtertentu. Para penginjil harus menemukan cara atau strategi yang efektif upaya Injil yangdiberitakan dapat diterima oleh pendengar. Penginjilan yang dilakukan secara khusus olehpenginjil Indonesia di beberapa daerah terpencil di Kalimantan Barat harus menerapkan modelpenginjilan yang efektis untuk mengatasi berbagai hambatan dalam penyampaian Injil.Kata kunci: penginjilan, model, hambatan dan solusi.